2021
DOI: 10.1177/13524585211020435
|View full text |Cite
|
Sign up to set email alerts
|

Mental health of people with multiple sclerosis during the COVID-19 outbreak: A prospective cohort and cross-sectional case–control study of the UK MS Register

Abstract: Background: People with MS (pwMS) have had higher rates of anxiety and depression than the general population before the COVID-19 pandemic, placing them at higher risk of experiencing poor psychological wellbeing during the pandemic. Objective: To assess mental health and its social/lifestyle determinants in pwMS during the first wave of the outbreak in the United Kingdom. Methods: This is a community-based, prospective longitudinal cohort and cross-sectional case–control online questionnaire study. It include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 38 publications
1
28
1
Order By: Relevance
“…While previous studies earlier in the pandemic found no differences in the mental health of PwMS who were COVID-19 positive versus not infected (Garjani et al, 2021), we found evidence of significant adverse mental health issues among PwMS who self-reported testing positive for COVID-19. In previous coronavirus outbreaks, high rates of depression and anxiety symptomatology have been found during the acute illness and post-illness stage among the general population (Rogers et al, 2020).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…While previous studies earlier in the pandemic found no differences in the mental health of PwMS who were COVID-19 positive versus not infected (Garjani et al, 2021), we found evidence of significant adverse mental health issues among PwMS who self-reported testing positive for COVID-19. In previous coronavirus outbreaks, high rates of depression and anxiety symptomatology have been found during the acute illness and post-illness stage among the general population (Rogers et al, 2020).…”
Section: Discussioncontrasting
confidence: 99%
“…Compared to PwMS in the United Kingdom in May-July 2020, the prevalence of moderate to severe depressive and anxiety symptoms in this U.S. cohort is marginally lower (27% versus 33% with moderate to severe depression and 15% versus 20% with moderate to severe anxiety) (Garjani et al, 2021). This may be due to differences in the baseline characteristics of the cohorts, differences in the study time frame, the societal and political response to the pandemic, and/or the announcement of the first COVID-19 vaccines in the U.S.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Depression as self-reported comorbidity exhibited a partial effect with respect to specific outcomes, such as the frequency of restricted access to appointments with MS specialists and behaviors, such as sexual dysfunction. Our findings are consistent with existing literature underlining a higher risk of anxiety and depression for PwMS relative to the general population and that these feelings are related to poor well-being during the pandemic ( 34 ). It should be stated, however, that in the frame of the present study, depression was not assessed by an online self-reported assessment tool, therefore a safe conclusion on the basis of discriminating the effect of current self-reported depressive feeling vs. a history of clinical diagnosis of depression on the reported outcomes is not possible.…”
Section: Discussionsupporting
confidence: 92%
“…During the pandemic, MS patients may experience enhanced anxiety or depression [ 59 ], worrying about the effect of MS drugs on the severity of COVID-19, and also the possible negative impact of COVID-19 on their disease. The patients could become overwhelmed by stigmatization, complicated by grief due to restrictions, uncertainty about the future, frustration, and socioeconomic issues [ 58 , 60 ].…”
Section: Cognitive Impact Of Covid19 On Ms Patientsmentioning
confidence: 99%